Homoclinic solutions of difference equations with variable exponents - Mihăilescu, Mihai; Rădulescu, Vicenţiu D.; Tersian, Stepan (Topological Methods in Nonlinear Analysis, 2011)
We study the existence of homoclinic solutions for a class of non-homogeneous difference equation with periodic coefficients. Our proofs rely on the critical point theory combined with adequate variational techniques, which are mainly based on the mountain-pass lemma.